2021
DOI: 10.1002/clc.23530
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of coronavirus disease 2019 in hospitalized patients with myocardial injury

Abstract: Background The clinical significance of Coronavirus disease 2019 (COVID‐19) as an associate of myocardial injury is controversial. Hypothesis Type 2 MI/Myocardial Injury are associated with worse outcomes if complicated by COVID‐19. Methods This longitudinal cohort study involved consecutive patients admitted to a large urban hospital. Myocardial injury was determined using laboratory records as ≥1 hs‐TnI result >99th percentile (male: >34 ng/L; female: >16 ng/L). Endotypes were defined according to the Fourth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…A study on 346 patients with elevated hs-cTnT conducted in the UK has demonstrated that there were no COVID-19-positive patients in the group of 115 patients with Type 1 MI, and in the group of 231 patients with Type 2 MI/myocardial Injury there were 36 (16%) patients who were COVID-19-positive. Cardiac causes of MI were more common in patients without SARS-CoV-2 virus (positive: 11.1% vs. negative: 33.3%, p = 0.22), of which tachyarrhythmia and heart failure were the most likely mechanisms (15.7% and 15.1%) [34]. Next, a study on 313 patients of whom elevation was present in 85 patients (27.2%) and of those 85 patients, only 11.7% had criteria for MI: 7% had type 2 MI, and 4.7% had type 1 MI [9].…”
Section: Myocardial Infarctionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on 346 patients with elevated hs-cTnT conducted in the UK has demonstrated that there were no COVID-19-positive patients in the group of 115 patients with Type 1 MI, and in the group of 231 patients with Type 2 MI/myocardial Injury there were 36 (16%) patients who were COVID-19-positive. Cardiac causes of MI were more common in patients without SARS-CoV-2 virus (positive: 11.1% vs. negative: 33.3%, p = 0.22), of which tachyarrhythmia and heart failure were the most likely mechanisms (15.7% and 15.1%) [34]. Next, a study on 313 patients of whom elevation was present in 85 patients (27.2%) and of those 85 patients, only 11.7% had criteria for MI: 7% had type 2 MI, and 4.7% had type 1 MI [9].…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…We used three articles in this section. Myocardial infarction in COVID-19-positive patients is not common [9,25,34]. A study on 346 patients with elevated hs-cTnT conducted in the UK has demonstrated that there were no COVID-19-positive patients in the group of 115 patients with Type 1 MI, and in the group of 231 patients with Type 2 MI/myocardial Injury there were 36 (16%) patients who were COVID-19-positive.…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…Cardiovascular injury is associated with history of prior cardiovascular disease, and elevated cardiac enzymes in the context of COVID-19 are associated with poorer outcomes compared with other causes of non-acute coronary syndromes or myocardial injury (140). Direct effect on the heart secondary to viral infiltration has been reported but appears to be uncommon (141).…”
Section: Myocardial Disease and Myocarditismentioning
confidence: 99%
“…Systemic pathogenic infection may pre-dispose to acute type 1 MI due to increased levels of circulating inflammatory cytokines in COVID-19 and resultant macrophage activity within atherosclerotic plaques, leading to coronary plaque rupture and thrombosis. Acute SARS-CoV-2 infection is also associated with a pro-thrombotic and pro-coagulable state; when combined with risk factors such as diabetes which is associated with impaired fibrinolysis and increased platelet activation, coronary thrombosis may occur(140).…”
mentioning
confidence: 99%
“…Troponin elevation in patients with COVID-19 not due to type 1 myocardial infarction is associated with greater mortality than non-COVID-19 causes of type 2 myocardial infarction or injury. 2 Given the prohibitive mortality in this higher-risk group, the data reflect a survival bias for patients surviving to discharge. Therefore, as Kotecha et al 1 point out, their study is focused to a small subgroup of patients with convalescent disease.…”
mentioning
confidence: 99%